2009
DOI: 10.1021/nl901553u
|View full text |Cite
|
Sign up to set email alerts
|

FRET Enhancement in Multilayer Core−Shell Nanoparticles

Abstract: This study describes the preparation and characterization of novel multilayer core-shell nanoparticles displaying metal-enhanced Forster resonant energy transfer. The increase in range and efficiency of Forster resonant energy transfer in these fluorescent nanocomposites and their vastly improved luminosity make them promising optical probes for a variety of applications such as cell imaging and biosensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
199
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(205 citation statements)
references
References 38 publications
4
199
0
2
Order By: Relevance
“…NPs plays a major role in wavelength and intensity of the plasmon resonance, another opportunity consists in combining a material that can un- [190]. Indeed, MEF is most efficient when the metal and the fluorophore are separated by several nanometers in order to avoid quenching by the metal.…”
Section: Metal In Dielectric Mediummentioning
confidence: 99%
“…NPs plays a major role in wavelength and intensity of the plasmon resonance, another opportunity consists in combining a material that can un- [190]. Indeed, MEF is most efficient when the metal and the fluorophore are separated by several nanometers in order to avoid quenching by the metal.…”
Section: Metal In Dielectric Mediummentioning
confidence: 99%
“…6,[19][20][21][22][23][24][25][26][27][28][29] LSP coupled FRET has been observed using single metallic nanoparticles coupled to a single donor-acceptor pair 6 , core-shell structures [23][24][25] and planar structures. [26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced local field generated by the plasmonic structures has also been shown to facilitate plasmon-enhanced nonradiative energy transfer. This has been demonstrated in a variety of material systems and geometries, with reported enhancements of the nonradiative energy transfer distance, rate and efficiency [26][27][28][29][30][31][32][33]. The possibility to achieve higher energy transfer efficiencies over larger distances allows for nonradiative pumping of a larger volume of QDs, and can potentially be exploited to improve the efficiency of nonradiatively pumped down-conversion for white LEDs.…”
Section: Introductionmentioning
confidence: 97%